Delegation, accountability & legislator moonlighting: Agency problems in Germany - Benny Geys; Karsten Mause (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2012)
Members of parliament in many countries are legally permitted to execute (un)paid jobs in addition to their political mandate. It is often argued that such moonlighting activities are unproblematic for the chain of democratic delegation and accountability as long as outside interests/earnings are disclosed to citizen-principals; the latter may then sanction (perceived) misconduct through the ballot box. Using principal-agent theory as an analytical framework and the German national parliament as a case study, this paper discusses why the accountability mechanisms of moonlighting disclosure and electoral control are often impaired in practice. We also illustrate that these concerns generalise beyond the German setting.
Keywords: 330; Abgeordnete; Nebentätigkeit; Prinzipal-Agent-Theorie; Wahlverhalten; Deutschland